Determinants of the Recurrences of Patients with Mental Disorders in the Psychiatric Polyclinic of Santo Vincentius Hospital, Singkawang - Maria Mardalena Sejong (UIMA Press, 2021)
Introduction: Mental disorders are very dangerous for someone even though they do not directly cause death, if not handled properly, will cause intense suffering for the individual and family. The biggest problem faced by patients with mental disorders and their families is recurrence caused by non-compliance with medication, family and environmental factors. Objectives: The research objective was to determine the effect of social support, socioeconomic, knowledge, family support, and medication adherence on relapse in mental patients. Methods: The research method used quantitative descriptive with cross-sectional design. The study population was all patients with mental disorders who visited the Psychiatric Polyclinic of Santo Vincentius Hospital in January 2019, totaling 600 people. The research sample consisted of 110 patients with mental disorders who were taken using the purposive sampling technique. The research instrument used a questionnaire, the results of which were analyzed using multivariate data. Results: The results showed that social support (p-value 0.031, odds ratio 3.253), socioeconomic (p-value 0.012, odds ratio 3.557), knowledge (p-value 0.033, odds ratio 2.966), family support (p-value 0.015, odds ratio 7,845), and medication adherence (p-value 0.041, odds ratio 3.045) affected the recurrence of mental disorders patients at the Psychiatry Polyclinic of Santo Vincentius Hospital 2020. Conclusion: The variable that had the greatest influence on the recurrence of mental disorders was family support. It is hoped that the family always strives to increase their support for patients by motivating patients, especially in taking medication, trying to meet the needs of patients in their treatment, and improving communication with patients.